1995
DOI: 10.1093/nar/23.18.3750
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coil,Saccharomyces cerevisiae, rat and human 3-methyladenine DNA glycosylases repair 1,N6-ethenoadenine when present in DNA

Abstract: The human carcinogen vinyl chloride is metabolized in the liver to reactive intermediates which generate various ethenobases in DNA. It has been reported that 1,N6-ethenoadenine (epsilon A) is excised by a DNA glycosylase present in human cell extracts, whereas protein extracts from Escherichia coli and yeast were devoid of such an activity. We confirm that the human 3-methyladenine-DNA glycosylase (ANPG protein) excises epsilon A residues. This finding was extended to the rat (ADPG protein). We show, at varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
166
3
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 204 publications
(176 citation statements)
references
References 31 publications
6
166
3
1
Order By: Relevance
“…The main repair pathway of ⑀dA is via 3-methyladenine DNA glycosylase that excises this exocyclic DNA base. 22,23 However, additional (nucleotide excision) repair pathways may operate in vivo that may liberate this adduct as deoxynucleoside, but this remains to be demonstrated. 1 Intervention group, n ϭ 29; control group, n ϭ 26.-2 Difference between pre-and post-intervention, p Ͻ 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…The main repair pathway of ⑀dA is via 3-methyladenine DNA glycosylase that excises this exocyclic DNA base. 22,23 However, additional (nucleotide excision) repair pathways may operate in vivo that may liberate this adduct as deoxynucleoside, but this remains to be demonstrated. 1 Intervention group, n ϭ 29; control group, n ϭ 26.-2 Difference between pre-and post-intervention, p Ͻ 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in vitro, repair by base excision repair proteins for edA occurs at a faster rate than that for edC, [43][44][45] leading to different adduct levels remaining in tissue DNA. If a nucleotide excision repair pathway eliminates the 2 etheno lesions from tissue DNA with a similar higher preference for edA, one would expect an inverse relation of the repair products in urine as was found indeed in the patients' urine.…”
Section: Random Generation Of Eda In All Liver Cell Nucleimentioning
confidence: 95%
“…The primary activity of these glycosylases, however, has generally been thought to remove N-3-and N-7-alkylated bases. Earlier Dosanjh et al (37) reported that eA is excised 10-to 20-fold more efficiently than 3mA by hANPG, whereas data from several other studies (28,38,39) showed that hANPG prefers 3mA over …”
Section: Excision Of Eamentioning
confidence: 94%
“…(27) This was confirmed shortly afterwards by Laval's group using a purified recombinant hANPG. (28) In addition, they showed that eA is removed by hANPG homologs in rat, yeast and E. coli. These activities are evolutionarily enhanced inasmuch as the mammalian glycosylases excise eA two to three orders of magnitude more efficiently than their yeast and bacterial functional homologs.…”
Section: Excision Of Eamentioning
confidence: 99%
See 1 more Smart Citation